2021
DOI: 10.3892/etm.2021.10357
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and survival of patients with three major connective tissue diseases associated with pulmonary hypertension: A study from China

Abstract: The present cross-sectional study investigated the clinical characteristics and survival of patients with three types of connective tissue disease associated with pulmonary hypertension (CTD-PH) diagnosed early by echocardiography. A total of 218 patients with CTD-PH were included in the present study. Patients with the three major types of CTD, namely systemic lupus erythematosus (SLE), systemic sclerosis (SSc) and primary Sjögren's syndrome (pSS), were included. PH was diagnosed based on pulmonary arterial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…PAH is a common and severe complication of SLE. 18 Noninvasive biomarkers are needed to help identify and risk‐stratify SLE‐PAH patients. In our study, we confirmed GDF‐15 as a useful biomarker of SLE‐PAH prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PAH is a common and severe complication of SLE. 18 Noninvasive biomarkers are needed to help identify and risk‐stratify SLE‐PAH patients. In our study, we confirmed GDF‐15 as a useful biomarker of SLE‐PAH prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…PAH is a common and severe complication of SLE 18 . Noninvasive biomarkers are needed to help identify and risk‐stratify SLE‐PAH patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of them were reviewed in full text to determine eligibility based on inclusion criteria. As such, 21 studies, [5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] involving 19 of them were included in the survival-relevant meta-analysis and 12 were included to analyze prognostic factors (Fig. 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…The discrepancies were chie y put down to the different diagnostic methods of transthoracic echocardiogram (TTE) and right heart catheterization (RHC). Other investigators estimated the prevalence of PH to be 2.7-17.5% based on TTE of SLE patients [8,9], while the prevalence of PH was 0.5-9.3% when diagnosed by RHC [10]. A meta-analysis in 2014 showed the prevalence of PAH in SLE patients among the Chinese population to be 1.8-23.3% [11], and the latest meta-analysis in 2018 showed a prevalence of 8% [12].…”
Section: Introductionmentioning
confidence: 99%